Effect of firing protocols on cohesive failure of all-ceramic crowns - Rues, Stefan; Kröger, Elke; Müller, Denise; Schmitter, Marc (Journal of dentistry, 2010)
Objectives - The mechanical properties of veneering material in all-ceramic restorations are inferior to those of high-strength ceramics. The objective of this study was to assess the effect of three different firing protocols (different cooling times) on cohesive failure of veneered all-ceramic crowns using a newly developed in vitro test design. - Methods - A prepared anterior maxillary incisor was used to produce geometrically identical crowns (n=68) with a zirconia framework 0.4mm thick veneered with two different ceramics and prepared by use of three different firing protocols. Twenty crowns were loaded until fracture without artificial ageing; the other crowns underwent thermocycling and chewing simulation before ultimate-load testing. Statistical analysis was performed using non-parametric tests. - Results - The results showed that a reduced temperature decrease after firing led to better performance of all-ceramic anterior crowns in the in vitro tests. A significant difference with regard to firing protocol (p=0.006) was observed for one veneering ceramic material only, however. - Conclusion - It can therefore be concluded that the test design presented enabled sensitive measurement of the effect of firing protocol on cohesive failure of all-ceramic crowns. The modified firing protocol with 6min additional cooling time resulted in greater resistance.
Gesehen am 22.06.2023